Public policies for youth in Brazil: a study of the young learning program (2005-2017) - Ribeiro, Luana Silva (Departamento de Economia, 2020)
Public policy has the dedication of facing a public problem, within this context, the aim of this article is to systematize, describe and analyze the Young Apprentice public policy in Brazil. The Young Apprentice is a program that ensures the opportunity for the young person in the labor market with benefits guaranteed by law. Firstly, a theoretical conceptual revision of public policies was carried out, later a historical approach to public policies for youth in Brazil, showing that during the Lula administration, several measures were taken in favor of youth, among them the National Youth Policy and the National First Job Program, and it was during this period that the Apprentice Law was strengthened. The evolution of the Young Apprentice program will be investigated sequentially. It is important to note that the Young Apprentice was effective in assisting groups with greater social vulnerability, guaranteeing the young person the first job, experience and professional qualification. But with the period of economic recession even with advantages to hiring apprentices, the program is in decline.